2023
DOI: 10.1007/s43450-022-00352-9
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin-3-O-rutinoside from Moringa oleifera Downregulates Adipogenesis and Lipid Accumulation and Improves Glucose Uptake by Activation of AMPK/Glut-4 in 3T3-L1 Cells

Abstract: Natural product-based therapeutic alternatives have drawn immense interest to deal with growing incidence of metabolic disorders. Rutin (quercetin-3- O -rutinoside) is found in a variety of fruits, vegetables, and plant beverages. In the present study, rutin was isolated from Moringa oleifera Lam., leaves and its anti-lipidemic and anti-adipogenic activity was evaluated through inhibition of key digestive enzymes and in vitro cell culture exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…For example, Q3G inhibits the production of IL-6 and TNF-α ( 48 ), as well as quercetin inhibits the inflammatory factors IL-1β and IL-6, and stimulates the secretion of the anti-inflammatory factor ( 49 ). Quercetin-3-O-rutinoside reduces glucose uptake by modulating the PPAR-γ signaling pathway ( 50 ). Chlorogenic acid also weakens disordered lipid metabolism through PPAR-α ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Q3G inhibits the production of IL-6 and TNF-α ( 48 ), as well as quercetin inhibits the inflammatory factors IL-1β and IL-6, and stimulates the secretion of the anti-inflammatory factor ( 49 ). Quercetin-3-O-rutinoside reduces glucose uptake by modulating the PPAR-γ signaling pathway ( 50 ). Chlorogenic acid also weakens disordered lipid metabolism through PPAR-α ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cyanidin-3- O -rutinoside could be involved in the effects of the cherry extract given this compound, the majority of which, can inhibit several enzymes in vitro , such as pancreatic cholesterol esterase and lipase, and reduce cholesterol uptake in Caco-2 cells . Similarly, rutin (quercetin-3- O -rutinoside), the main phenolic compound in the apricot extract, also inhibited pancreatic lipase in vitro and reduced the lipid content and adipogenesis of 3T3-L1 cells . Total cholesterol levels have also been shown to be modulated by ellagitanins present in the pomegranate extract when administered to rats fed a high fructose diet .…”
Section: Discussionmentioning
confidence: 99%
“…As the major metabolite of rutin, quercetin can increase the potential of anti-steatosis in the liver of rat by reducing the activity of hepatic lipogenic enzymes and activating the cytoplasmic lipase adipose triglyceride lipase (ATGL) activity ( 45 ). Administration of rutin in adipocytes inhibits the activity of alpha-glucosidase and pancreatic lipase and increases adiponectin levels in vitro ( 46 ). To the best of our knowledge, this is the first study on the effect of rutin on hepatic lipid metabolizing enzymes in laying hens, and the results showed that dietary rutin could reduce the activities of ACC and ME in the liver of aged laying hens.…”
Section: Discussionmentioning
confidence: 99%